2018
DOI: 10.1177/1362168818777518
|View full text |Cite
|
Sign up to set email alerts
|

Reframing teaching knowledge in Content and Language Integrated Learning (CLIL): A European perspective

Abstract: CLIL (Content and Language Integrated Learning) is a recent teaching approach widely adopted in numerous international contexts, especially in Europe where it was promoted as a way to promote language learning within the educational system. When implemented, CLIL predominantly involves subject content teachers using English to teach their subject. This has required the development of specific teacher education programs in Italy. This contribution illustrates how the teaching knowledge of both content and Engli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 32 publications
(56 reference statements)
0
14
0
1
Order By: Relevance
“…With the growing demand for English, the use of EMI in content‐area subjects is believed to be a more efficient way than the traditional foreign language approach to provide functional proficiency in an L2 (Lopriore, 2020). Research has shown that EMI students tend to have a better knowledge of English vocabulary (e.g., Aizawa & Rose, 2020; Chan, 2014; Lo & Murphy, 2010) and enhanced receptive linguistic competence (e.g., Dalton‐Puffer, 2008; Yang, 2015).…”
Section: Language Learning In Emi Educationmentioning
confidence: 99%
“…With the growing demand for English, the use of EMI in content‐area subjects is believed to be a more efficient way than the traditional foreign language approach to provide functional proficiency in an L2 (Lopriore, 2020). Research has shown that EMI students tend to have a better knowledge of English vocabulary (e.g., Aizawa & Rose, 2020; Chan, 2014; Lo & Murphy, 2010) and enhanced receptive linguistic competence (e.g., Dalton‐Puffer, 2008; Yang, 2015).…”
Section: Language Learning In Emi Educationmentioning
confidence: 99%
“…El aprendizaje integrado de contenidos y lenguas (CLIL) supone un gran desafío para el profesorado, tanto en los que todavía están en formación como los docentes en ejercicio, en muchos aspectos tales como la innovación y el aprendizaje permanente (Lopriore, 2020). El desarrollo de un currículum de formación del profesorado en CLIL es una tarea exigente y difícil debido a su naturaleza integradora (Coyle, 2018; Navarro-Pablo, López-Gándara, & García-Jiménez, 2019).…”
Section: Bilingüismo E Intercultura: ¿Qué Están Haciendo Los Docentes?unclassified
“…Content and Language Integrated Learning (CLIL) implies an enormous challenge for both pre-service and in-service teachers in several respects, such as innovation and lifelong learning (Lopriore, 2020). The development of a teacher-training curriculum in CLIL is a demanding and difficult task because of its integrative nature (Coyle, 2018; Navarro-Pablo, López-Gándara, & García-Jiménez, 2019).…”
mentioning
confidence: 99%
“…In Europe, recent reports showed that this current educational approach has been integrated into the education system in more than 40 European countries to different educational levels. Further, such as in Italy and the Netherlands, CLIL has been institutionalized in the national educational curriculum (Lopriore, 2018;van Kampen et al, 2018). Italian secondary schools officially introduce CLIL approach as a part of their national curriculum.…”
Section:  Introductionmentioning
confidence: 99%